Is the export-led growth hypothesis valid for sri lanka? A time series analysis - Francis, S.J.; Vijayakumar, S. (Proceedings of 9th International Symposium, 2019)
The export-led growth (ELG) hypothesis suggests that there is a strong positive linear relationship between a country’s exports and economic growth. For many years, theoretical and empirical studies have examined the causal relationship between exports and economic growth and found that this relationship is one of interdependence rather than of unilateral causation. This paper intends to investigate the casual effects of short and long run relationship between Export and Economic Growth and determine the recent trends, developments and obstacles Exports in Sri Lanka. The paper builds its analysis on the available literature on theoretical and empirical forecasting and applies on Sri Lanka Export Market. Annual time series data on Gross Domestic Production, Export, Gross fixed capital formation, employment and inflation, which cover the 1977– 2018 period, have been used in this study for the analysis. The data are taken from sources such as economic surveys of Sri Lanka, World Bank Reports, Central Bank Reports of Sri Lanka, UNCTAD (United Nations Conference on Trade and Development) Reports, and IMF reports. All data figures are expressed in rupees millions, unless otherwise percentage. The main purpose of this study employed empirical econometrics time series analysis Export –led growth hypothesis for Sri Lankan by testing using ADF unit root test, Johansen Co integration test, Vector Error Correction (VEC) modelling and Granger casualty test. Ordinary Least Square method (OLS) is used to estimate and explain the regression model of the study. The findings of this article reveal that export which promotes economic growth, capital investment and employment in the short- and long-run for Sri Lanka. We find that the reported results confirm the validity of export-led growth hypothesis for Sri Lanka. That is, openness indeed leads to higher economic growth.
Keywords: Export led growth; Co-integration test; Openness; Trade liberalization